KETERAMPILAN BERBICARA SISWA SEKOLAH DASAR MELALUI PROJECT BASED LEARNING - Fajjar Ajrin Astiar; Rarasaning Satianingsih; Via Yustitia (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
Students need speaking skill when they are in front of the class to express their opinions. However, many students are still not confident to speak. This research objective was to see whether the students who were taught by PjBL model had better speaking skill than the students who were taught by cooperative learning model. This research was quasi-quantitative experimental research with Posttest-Only Control design. The population of this research were the fifth-grade students at SDN Gayungan II Surabaya. The samples were chosen by using cluster random sampling technique and class V-A was selected as the experiment class and class V-B was chosen as the control class. The data were collected through tests, observation, and documentation. The data derived from the tests were analyzed by using inferential statistics with SPSS software. Then, the data from students’ activities and the learning implementation were analyzed by using descriptive statistics. The results showed that the students who were taught by PJBL model significantly had better speaking skill than the students who were taught by cooperative learning model.